2005
DOI: 10.1093/gerona/60.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Enriched Drink on Cognitive Function in Frail Elderly Persons

Abstract: This study contributes to the evidence that nutritional supplementation may improve neuropsychological performance in frail elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Nevertheless, cognitive improvement has been found after homocysteine levels were lowered (54,55). Depression has been relieved by lowering homocysteine levels with B vitamin supplementation (56).…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Nevertheless, cognitive improvement has been found after homocysteine levels were lowered (54,55). Depression has been relieved by lowering homocysteine levels with B vitamin supplementation (56).…”
Section: Intervention Studiesmentioning
confidence: 99%
“…The possibility that those at increased risk of nutritional deficiency may benefit from supplements is supported by the FACIT study of men and women aged 50–70 y with elevated homocysteine in whom there were significant effects on global cognitive function, though for specific cognitive domains the effects were seen in memory (assessed by recall of 15 common words) and information processing speed (assessed by letter-digit substitution) but not in verbal fluency (assessed by asking the subjects to name as many animals as possible in one minute) or in sensorimotor speed or complex speed [9]. The possibility of a beneficial effect in higher risk subjects is also supported by the study of Dutch care home residents with a BMI less than 25 kg/m 2 and median age of 83 y which found beneficial effects of multivitamins and multiminerals in a test of short-term memory and one of two tests of category fluency [12]. The clinical significance of the differences in the verbal fluency test scores between supplemented and placebo groups seen in the present study is difficult to estimate as the tests are not widely used in clinical practice, but data from a cross-sectional study of Canadian adults suggest that the rate of decline in performance on this test is of the order of one point per 3 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, intervention studies with antioxidant vitamins [2-5] or B vitamins [6-8] given for 24 weeks or more in community-living older people have found no evidence for a beneficial effect of supplements, though a recent study of subjects with raised homocysteine levels found a significant benefit of folic acid supplementation for 3 years on global cognitive function and two of the five component cognitive domains [9]. Two randomised trials which used multivitamins for 24 weeks or more also found no evidence of a beneficial effect [10,11] but a small trial of frail elderly people in residential care found a beneficial effect of multivitamin and multimineral supplementation in two of the five tests of cognitive function after six months [12]. Another trial of a multivitamin and multimineral supplement in healthy elderly subjects reported beneficial effects after one year in six of seven tests [13], though these findings have recently been retracted in the light of concerns about the veracity of the data and possible conflicting commercial interest [14].…”
Section: Introductionmentioning
confidence: 99%
“…83 On the other hand, in a small study of a supplement providing energy and micronutrients, some significant improvements were seen after six months. 84 Studies that have used folic acid, vitamin B12, and vitamin B6, three of the vitamins most likely to improve cognitive function, found no evidence for any improvement of cognition or dementia. 85 Moreover, a recent study by Rayman and coworkers 86 strongly suggests that in contrast with previous reports, selenium supplementation does not improve mood or quality of life in healthy volunteers.…”
Section: Infections In the Elderly Populationmentioning
confidence: 99%